Biopromoters for Gas Hydrate Formation: A Mini Review of Current Status - Zhang, Yong-Tao; Chen, Fu-Lin; Yu, Shi-Jie; Wang, Fei (Frontiers in Chemistry, 2020)
Gas hydrates have promising application prospect in field of future energy source, natural gas storage and transportation, CO2 capture and sequestration, gas separation and cold energy. However, application of hydrate technology is being restricted due to slow formation rate of gas hydrate. Kinetic promoters get increasing attention, given that they can improve hydrate formation rate with very small dose and do not affect gas storage capacity. However, most of kinetic promoters are non-renewable, petrochemical-derived, non-degradable materials, inevitably leading to resource waste and environmental pollution. Biopromoters, derived from biomass, are renewable, biodegradable, environmentally friendly, nontoxic (or low toxic), and economically feasible. This mini review summarizes current status of already discovered biopromoters, including lignosulfonate, amino acid, biosurfactant and biological porous structure, which have potential to replace petrochemical-derived promoters in hydrate technology. Finally, Future research directions are given for the development of biopromoters.